﻿Distribution, conservation assessment and management perspectives of Chilean micro-snails of the family Charopidae - Gonzalo A. Collado; Nataly Flores; Marcela A. Vidal; Cristian Torres-Díaz; Moisés A. Valladares (Nature Conservation, 2023)
The biodiversity of molluscs is highly threatened in marine, terrestrial and freshwater ecosystems worldwide. This research aimed at studying the distribution and conservation status of eight poorly-known micro-snails of the genera Stephacharopa and Stephadiscus in Chile. We performed a comprehensive review of literature and databases to determine the occurrences of the species, which were mapped on vector layers containing protected areas and human development infrastructure to find potential threats. Conservation status assessment was performed following the criteria and tools implemented by the International Union for the Conservation of Nature (IUCN) Red List and NatureServe. We also conducted species distribution models, based on maximum entropy, to identify areas that should be prioritised for conservation. Two species meet the criteria for IUCN listing as Critically Endangered (CR), four Endangered (EN), one Vulnerable (Vu) and one Least Concern (LC). This classification is rather coincident with equivalent categories obtained under the NatureServe standard, in which two species were ranked as Critically Imperiled (N1), five Imperiled (N2) and one Vulnerable (N3). We found that Stephacharopa paposensis is the most at-risk species, with only one occurrence not included in a protected area, followed by Stephadiscus stuardoi, with two occurrences, one of them within a protected area. Stephadiscus lyratus was the species with the greatest geographic range, accounting for 17 occurrences, seven matching a protected area. We found wider potential ranges in modelled species that may be useful for prioritising conservation measures. Considering distributional data, protected areas and more than 20 plausible threats identified, we propose potential in situ and ex situ conservation actions to protect these neglected micro-snails.